Competence Approach in the Philosophy of Education: Capabilities and Problems - Proleiev, Serhiy; Shamrai, Victoria (Filosofiya osvity. Philosophy of Education, 2017)
This article analyzes the potential and problems of determining the content of education based on competencies. Were identified the main impacts of this process. Particular attention is paid to the implementation of the principle of comparability in the construction of modern educational standards. Analyzed the contradictions of General competences of the project Tuning. In the two tables are integrated contradiction competence on three educational levels and general competencies two lists of project Tuning.